Citation Pattern of Agricultural Extension Researchers in Nigerian Journals - T A Adetunji; J O Oladeji; T O Olowu (Journal of Agricultural Extension, 2015)
The study investigated the citation pattern of agricultural extension researchers in extension journals over a ten -year period. Seven journals were content analysed for categories of extension specializations, self citation, infra -and inter -institutional citation. Findings reveal that rural sociology articles are the most published in extension journals. Self citation is low among extension researchers while inter -institutional citation is higher than intra- institutional citation. However, infrainstitutional citation was more predominant during the pre -AESON period.